10-Gingerol Suppresses Osteoclastogenesis in RAW264.7 Cells and Zebrafish Osteoporotic Scales - Zang, Liqing; Kagotani, Kazuhiro; Nakayama, Hiroko; Bhagat, Jacky; Fujimoto, Yuki; Hayashi, Akihito; Sono, Ryoji; Katsuzaki, Hirotaka; Nishimura, Norihiro; Shimada, Yasuhito (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis is the most common aging-associated bone disease and is caused by hyperactivation of osteoclastic activity. We previously reported that the hexane extract of ginger rhizome (ginger hexane extract; GHE) could suppress receptor activator of nuclear factor kappa-B ligand-induced osteoclastogenesis in RAW264.7 cells. However, the anti-osteoclastic components in GHE have not yet been identified. In this study, we separated GHE into several fractions using silica gel column chromatography and evaluated their effects on osteoclastogenesis using a RAW264.7 cell osteoclast differentiation assay (in vitro) and the zebrafish scale model of osteoporosis (in vivo). We identified that the fractions containing 10-gingerol suppressed osteoclastogenesis in RAW264.7 cells detected by tartrate-resistant acid phosphatase staining. In zebrafish, GHE and 10-gingerol suppressed osteoclastogenesis in prednisolone-induced osteoporosis regenerated scales to promote normal regeneration. Gene expression analysis revealed that 10-gingerol suppressed osteoclast markers in RAW264.7 cells (osteoclast-associated immunoglobulin-like receptor, dendrocyte-expressed seven transmembrane protein, and matrix metallopeptidase-9 [Mmp9]) and zebrafish scales (osteoclast-specific cathepsin K, mmp2, and mmp9). Interestingly, nuclear factor of activated T-cells cytoplasmic 1, a master transcription regulator of osteoclast differentiation upstream of the osteoclastic activators, was downregulated in zebrafish scales but showed no alteration in RAW264.7 cells. In addition, 10-gingerol inhibited cathepsin K activity under cell-free conditions. This is the first study, to our knowledge, that has found that 10-gingerol in GHE could suppress osteoclastic activity in both in vitro and in vivo conditions.